2013
DOI: 10.1080/10615806.2013.763934
|View full text |Cite
|
Sign up to set email alerts
|

The effect of induced self-presentation concerns on cognitive appraisal and affect

Abstract: An experiment was conducted to investigate how self-presentation imperatives can influence cognition and affect. Participants were 70 collegiate and recreational athletes who were recruited because of the relevance of self-presentation processes in sport. Athletes were asked to read either a script which de-emphasized self-presentation concerns (low self-presentation) or emphasized self-presentation concerns (high self-presentation). The scripts were developed for the purpose of the study and depicted a pre-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…A majority of the studies appeared to test predictions 2 and 3, examining the associations between self-efficacy, perceptions of control, and achievement goals, using self-report measures or interviews (for example, Howle and Eklund, 2013;Meijen et al, 2013). Meijen et al (2013) found that avoidance goals were positively related to a threat perception, and approach goals and self-efficacy negatively predicted a threat perception.…”
Section: The Predictions Of the Theory Of Challenge And Threat Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of the studies appeared to test predictions 2 and 3, examining the associations between self-efficacy, perceptions of control, and achievement goals, using self-report measures or interviews (for example, Howle and Eklund, 2013;Meijen et al, 2013). Meijen et al (2013) found that avoidance goals were positively related to a threat perception, and approach goals and self-efficacy negatively predicted a threat perception.…”
Section: The Predictions Of the Theory Of Challenge And Threat Statesmentioning
confidence: 99%
“…In practical terms, this may be an athlete who decides to avoid going into a tackle at a rugby match. Although there were no experimental studies focusing on this prediction, Howle and Eklund (2013) found that a challenge state was associated with lower avoidance goals.…”
Section: The Predictions Of the Theory Of Challenge And Threat Statesmentioning
confidence: 99%
“…Several studies such as Coetzee et al (2006), Cox et al (2010) and Elferink-Gemser (2005) emphasize the importance of psychological characteristics for success in elite sports. Hook, Valentiner and Connelly (2013), Howle and Eklund (2013), think of sports performance as of a situation of evaluation, which is influenced by emotional and cognitive factors. This is why, according to what has already been said and agreeing with Fletcher and Scott (2010), personal characteristics as well as the situational and cultural objectives of the athletes are factors to be considered.…”
Section: Emotions and Concentrationmentioning
confidence: 99%
“…Performance is a sport outcome undoubtedly regulated and influenced by mental factors ( Howle and Eklund, 2013 ). The abilities connected with regulating arousal, processing information and managing emotions are crucial determinants of performance for competitive athletes ( Thomas et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%